KONVERGENSI IFRS DAN PELUANG PRAKTIK MANAJEMEN LABA DI INDONESIA: SEBUAH LITERATUR REVIEW - Arief Hidayatullah Khamainy (Fakultas Ekonomi dan Bisnis, 2021)
Earnings management practices result in the fact that the economic conditions in the company's financial statements are not actually presented so that the profits that are expected to provide information to support decision making are doubtful. The existence of IFRS encourages managers to perform high-quality financial reporting, resulting in high-quality earnings as well. This paper aims to analyze the opportunities for earnings management practices after IFRS convergence in Indonesia. The secondary data used in this literature study were obtained from empirical studies on the convergence of IFRS and earnings management in Indonesia. The results of the analysis show that the opportunity for earnings management practices will exist, both after the convergence of IFRS, so the importance of supervision carried out by investors to obtain reliable financial information as a basis for decision making.